Providing Information and Computer Support Teaching Ecological Disciplines - Солошич, І. О.; Почтовюк, С. І. (Man and Environment. Issues of Neoecology)
Purpose. Quality Analysis of collateral information and computer support teaching environmental sciences direction. Methods. Methods of theoretical study (analysis and synthesis). Results.The article deals with the use of various means of information and communication technologies in the process of independent research in the future environmental specialists. The basic directions of the group to use them to effectively address problems related to acquisition of knowledge and the formation of scientific and practical skills in the students. Conclusions. Instant access to information and transfer, mobility, interaction between students and a teacher training to improve performance.